If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(17 + -8) = x + -8 Combine like terms: 17 + -8 = 9 x(9) = x + -8 Reorder the terms for easier multiplication: 9x = x + -8 Reorder the terms: 9x = -8 + x Solving 9x = -8 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 9x + -1x = -8 + x + -1x Combine like terms: 9x + -1x = 8x 8x = -8 + x + -1x Combine like terms: x + -1x = 0 8x = -8 + 0 8x = -8 Divide each side by '8'. x = -1 Simplifying x = -1
| (2+4y)-(y+9)=20 | | .12y+0.06(y+2000)=1020 | | 2x+90+90+x=360 | | 0.5(0.5y-0.5)= | | 20x+12=172 | | 8x-5x=5x-2 | | 8(10n-10)+3= | | 1/2(30)(36) | | 7x-6(5x+3)=-156 | | 3x-9x+18=18x | | c/2+4=6 | | w^2+2wp-35p^2=0 | | n+33/2=57/9 | | -2(3x+1)=3(4x+1) | | -2n+12=54 | | 2(3+2x)=-6 | | -5(7-5r)=19-2r | | 6/7x-1/4x+10-11/14x | | -4y+10=-3+10y | | x+1/x-2=4/7 | | 0.6666667a-0.75=0.75a | | 3m=20-2m | | 4p-3p= | | a+13=2a-7 | | (x+2)(X+-1)(x+2i)=0 | | -2(a-8)=16-a | | -4x=-50-2 | | 5x+2(3-x)+1=11 | | -6y+4(y+5)=36 | | 1/6p=1/3 | | -6x=6(1-x) | | -6x^6-18x^5+60x^4=0 |